An enhanced techno-economic analysis of LCOE: public incentives vs private investment - Peón Menéndez, Rogelio; Parra Martín, Alejandro; Varela-Candamio, Laura; García-Álvarez, María-Teresa (Technological and Economic Development of Economy, 2021)
This paper offers a new approach for the estimation of levelized cost of energy (LCOE) by considering the shareholder internal rate of return (IRR) as an unexplored measure in this kind of analysis. The study relies on a comprehensive techno-economic evaluation based on interactions among a set of factors. This mathematical model is then empirically tested for a CSP power plant in Extremadura (Spain) due to their dominant market position and also for being the most developed renewable system at the present. A sensitivity analysis is also performed to establish the influence that market conditions have on the determination of LCOE for different scenarios under the maintenance of a given shareholder IRR for investors. This last assumption makes investment decisions indifferent among several projects in order to focus solely on the minimization of the LCOE. Results reveal that while the annual net electricity production contributes to the reduction of LCOE, total investments, equity percentage and operation and maintenance (O&M) costs help to increase their value by a high percentage. This study gives important scientific basis for investment decision making and also becomes a standpoint to design suitable public incentives that may enhance future technological developments in the CSP generation industry.First published online 27 February 2020